ANALISIS PENGARUH DIMENSI PELAYANAN PRIMA TERHADAP KEPUASAN NASABAH TABUNGAN BRI KANTOR CABANG KENDAL - Ayu Rosefiani Syara; Jati Handayani (KEUNIS, 2020)
This study aims to determine the dimensions of service excellence consists of ability, attitude, appearance, attention, action, and accountability toward Customer Satisfaction Savings at PT Bank Rakyat Indonesia (Persero) Tbk. Branch Office Kendal.Testing method of data that used in this study was to test the validity, reliability test, normality test, multicoloniarity, test heteroskedastisitas, autocorrelation test, test analysis linear multiple, F test, t test, and test the coefficient of determination (R2) which shows the can used to measure customer satisfaction savings.Multiple linear regression method yields customer satisfaction equation = -0,937 + 0,346Ability + 0.226Attitude + 0.179Appearance + 0.207Attention + 0,381Action + 0,294Accountability + e. In F test, it is found that the dimensions of service excellence Ability, Attitude, Appearance, Attention, Action, and Accountability simultaneously have significant influence to Customer Satisfaction Savings at PT Bank Rakyat Indonesia (Persero) Tbk. Branch Office Kendal. The result of t test is influence Ability, Attitude, Appearance, Attention Action, and Accountability have significant influence to Customer Satisfaction Savings at PT Bank Rakyat Indonesia (Persero) Tbk. Branch Office Kendal.